BRAZILIAN’S PERSPECTIVE ABOUT ADOPTION INTENTION AND EFFECTIVENESS OF DIGITAL PLATFORMS FOR ONLINE LEARNING DURING COVID-19 - Márcia Maria dos Santos Bortolocci Espejo; Iasmin Alencar de Andrade; Núbia Gabriela de Oliveira Kawai; Guilherme Alves de Souza Andrade; André Felipe Queiroz (Encontro Internacional de Gestão, Desenvolvimento e Inovação (EIGEDIN), 2022)
Due to the social isolation imposed by the Covid 19 pandemic, many higher education institutions had to abruptly switch from face-to-face to online university instruction. Although distance education was a reality before the pandemics, the timely transition from traditional teaching to online teaching requires a complex approach to effectively integrate this system. Therefore, the purpose of this study is to identify the factors that influence the adoption of technological tools by business students during the pandemics. The methodology used for the research was quantitative with the submission of an online quiz to students of a Brazilian university. The results show that the perceived usefulness and the perceived ease of use of a technological tool do not have a positive influence on students' attitudes towards its use, while a positive relationship was found between the interactivity and the cost-benefit ratio of the platforms and students' attitudes. Therefore, it can be concluded that offering a digital teaching platform with resources that allow high interaction between students and instructors and that do not involve high costs for students can help to increase the willingness to use the platform.